Nutrire il pianeta, alimentare la speranza (Glocalism: Journal of Culture, Politics and Innovation, 2014)
The long-lasting crisis has produced a new inequality: in the advanced societies, the numbers of people below the poverty threshold are on the increase and in the world one person in eight does not have enough food to have a healthy, active life; every year, deaths due to starvation are in the millions. This situation is even more shocking if we set it against the issue of “waste”: every year the industrialised countries throw around 1.3 billion tons of food, equal to one third of the world’s production and more than half the planet’s cereal crops, into the rubbish bin.The theme of Expo 2015, “Feeding the Planet. Energy for Life”, fits into the context of this reality and will be remembered to the extent to which it is able to provide ideas, favour agreements, launch projects to create sustainable economies and useful collaborations in order to emancipate the poorest countries from the slavery of hunger at least a little. In this perspective, globalisation does not diminish the role of cooperation and in many situations it may indeed favour it, increasing its weight and value. It is necessary, however, to identify new and more structured approaches, alongside the traditional methods.The Università Cattolica del Sacro Cuore is operating in various nations of the world with international solidarity projects and experience confirms that it is unthinkable to act in isolation in providing responses to each situation of need. Cooperation, furthermore, must be able to avail itself of leaner legislation and institutions and governments that are quicker and more secure in sustaining it. The quality of the political response in fact facilitates and increases the private initiative that is indispensable to the spirit and action of cooperation.
Keywords: poverty; food; sustainable economies; cooperation; solidarity